Monsanima tinguaensis (Apocynaceae), an enigmatic new species from Atlantic rainforest - Silva, Uiara Catharina Soares; Santos, Renata Gabrielle Pinheiro; Rapini, Alessandro; Fontella-Pereira, Jorge; Liede-Schumann, Sigrid (Phytotaxa, 2014)
A new species of Asclepiadoideae (Apocynaceae) with enigmatic taxonomic position was found in the Atlantic rainforest of Rio de Janeiro State, southeastern Brazil. To ascertain its affinities within the Asclepiadeae, we performed phylogenetic analyses using the plastid regions trnT-L and rps16. Our results strongly support the new species close to the Orthosiinae, but do not support any generic relationship for this species. Based on the floral morphology, especially the corona lobes, which are highly fused, and curved inward at the top, covering the gynostegium, the new species is assigned to Monsanima. This genus is sister to the other Orthosiinae and included so far only one species narrowly endemic to the campos rupestres of Bahia, in northeastern Brazil. The new species, Monsanima tinguaensis, occurs in a protected area, Tinguá Biological Reserve. However, it is known only by the type specimen and is probably vulnerable to extinction.